Registros de Parina Grande (Phoenicopterus andinus) en la laguna Melincué, Santa Fe, Argentina - Romano, Marcelo; Pagano, Fernando; Luppi, Marcelo (Nuestras Aves, 2002)
Este artículo no cuenta con un resumen.